#TITLE_ALTERNATIVE# - ELPIN. S (NIM : 13706040); Pembimbing 1 : Dr. Ir. Husaini Ardy ; Pembimbing 2 Dr. Eng. Budi Pra, AGUS
Solid particle erosion is a phenomenon of material exfoliation because of repeated collisions of solid particles on the material surface. The damage can decrease the effectiveness application of the material and can make material failure. Modification the material surface can prevent unexpected effect from this phenomenon. One method of surface modification is a thermal spray coating . This method has been widely used in industry and engineering as the application to increase erosion resistance of materials. High velocity oxyfuel and electric wire arc spraying were used as a method of thermal spray coatings. Two types of feedstock were used as a coating material. HVOF process used feedstock powder WC-12% Co -63 μm (-230 mesh) which blended with NiCr powder -106 μm (-140 mesh) while the Fe-WC electrode wire 1.6 mm is used as a feedstock wire electric arc spraying . Solid particle erosion testing performed on Fe-WC and WC-12% Co + NiCr coating with three different erosion angles 30Ã‚Â°, 60Ã‚Â° and 90Ã‚Â°. Weight loss of material because of solid particle erosion became analysis of erosion rate. The mechanism of erosion was determined through analysis of scanning electron microscope images on the coating surface. Surface rougness test was done to compare the surface roughness material before and after solid particle erosion testing. Beside solid particle erosion testing, impact strength of the coating and its failure model was also investigated using a repeated impact test. Erosion rate of WC-12% Co + NiCr coating was lower than the Fe-WC coating with the highest erosion rate occurred at angle of 900 for both coating. Brittle erosion mechanism has occured on the Fe-WC coating. Combination of brittle and ductile erosion mechanisme has occured on the WC-12%Co-NiCr coating. The impact test using repeated impact test method. Number of impact to failure has became reference of the impact strength for this method. The result of this method showed 108 number of impact cycles to failure on Fe-WC coating and around 54 cycles for WC-12%Co-NiCr coating. Through the appearance of macro and micro structure photographs, adhesive bond failure has occured on WC-12%Co-NiCr coating and kohesive bond failure has occured on Fe-WC coating.